1997
DOI: 10.1111/j.1574-695x.1997.tb01020.x
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and phenotypic determination of five virulence markers in clinical isolates ofEscherichia coli

Abstract: The presence of the virulence markers K1 capsule, serum resistance, aerobactin, S and P/PR fimbriae were examined in a total of 395 E. coli strains from different extraintestinal infections and in 81 faecal isolates of healthy volunteers using specific DNA probes and classical phenotypic methods. All markers were more frequently detected when genotypic assays were applied. The simultaneous occurrence of 3–4 virulence determinants was typical for isolates derived from patients with septicaemia or meningitis. Is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…Many authors have demonstrated that the majority of neonatal meningitis cases are due to K1-positive E. coli , while other authors have reported that these particular strains are less frequent in vaginal tracts, in a similar proportion between pregnant and non-pregnant women [ 10 , 33 , 34 , 35 ]. Some authors have demonstrated, using DNA hybridization methods, that virulence patterns (including K1-capsules) of strains isolated from blood culture and cerebrospinal fluid were different from those of urogenital strains [ 36 ]. This observation is nowadays contested, due to similar representation, as in the present study, of K1-positive and K1 negative strains (40% and 60% approximately in the present study).…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have demonstrated that the majority of neonatal meningitis cases are due to K1-positive E. coli , while other authors have reported that these particular strains are less frequent in vaginal tracts, in a similar proportion between pregnant and non-pregnant women [ 10 , 33 , 34 , 35 ]. Some authors have demonstrated, using DNA hybridization methods, that virulence patterns (including K1-capsules) of strains isolated from blood culture and cerebrospinal fluid were different from those of urogenital strains [ 36 ]. This observation is nowadays contested, due to similar representation, as in the present study, of K1-positive and K1 negative strains (40% and 60% approximately in the present study).…”
Section: Discussionmentioning
confidence: 99%
“…Важность жгутикового аппарата была подтверждена экспериментально: при нарушении функции генов, кодирующих такие белки, как FliD, FlaA и FlaB, происходит снижение способности H. pylori к колонизации слизистой оболочки желудка [13,14]. Важную роль в этом процессе также играет хемотаксис на различные молекулы-хемоаттрактанты: муцин, бикарбонат натрия, мочевину и различные аминокислоты, которые распознаются хеморецепторами возбудителя T1pA, B, C и D, CheA киназой и другими, существование которых установлено в многочисленных экспериментальных исследованиях [13,15,16,17].…”
Section: результаты б иологические особенности H Pylori и патогенез хеликобактерной инфекцииunclassified
“…The pathogenesis of E. coli pyelonephritis is complex, involving the interaction of several factors present in the host and in the invading organism. Host factors predisposing to PN can be anatomic, increased uroepithelial cell adherence, and nonsecretion of P blood group or of the Lewis blood group antigens[4]. Previous investigations have indicated that various virulence factors, such as pili associated with pyelonephritis (pap), afimbrial adhesin I, haemolysin (hly) and cytotoxic necrotizing factor 1 (cnf 1) are useful markers for the detection of uropathogenic E. coli and could therefore be used in the diagnosis of PN[5–7].…”
Section: Frequency Of O Groups In Children With Urinary Tract Infectimentioning
confidence: 99%